Nutritional Minerals and Heavy Metals in Tea Infusions and Daily Intake of Human Body - Ayse Dilek Atasoy; Mehmet Irfan Yesilnacar; Ali Yildirim; Ahmet Ferit Atasoy (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Tea (Camellia sinensis) is one of the most popular nonalcoholic beverages in the world. During tea infusion, both essential mineral elements and toxic metals are extracted into the beverage. In oriental countries, almost a liter of tea is consumed daily by an average adult. Thus, high toxic elements in traditional teas can be of concern. Aim of the study was to determine the essential element contents and toxic heavy metal concentrations in tea products available on the market in Turkey and comparing the contents of infusion for Turkish and Ceylon black and green tea types. The associated health risk to tea drinkers were estimated with reference to Tolerable Daily Intake (TDI) Values from US EPA for adults and children. Among the essential elements in all of the black teas purchased from the market, K was present at the highest concentration followed by Mg, Ca and Al. Pb and Mn contents of several tea samples were found over the Tolerable Daily Intake levels.